WORD FORMATION IN SELECTED LYRICS WRITTEN BY ASIAN SONGWRITERS - Merih Handayani; Evi Jovita Putri; Nico Harared (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
The aim of the study is to explore the type of word-formation process in Selected Lyrics Written by Asian Songwriters. The form of this research was a qualitative method thus the result was conducted in descriptive. The data were taken by sorting out the English song written by Asian songwriters which were released around 2018-2021 and have at least 3 million listeners on an online streaming platform then making the transcript of the lyrics. The focus of this research is to find out and analyze word-formation process using Yule's theory (2010) and Plag (2002) as supporting theories. As the result, there are 8 processes of word-formation, and the most prominent lyrics are formed through Inflectional with 45 data then followed by Compounding 27 data, Derivation 25, Multiple Processing 24 data, Clipping 11 data, Blending 8 data then Acronym and Conversion that has 6 data of each.